PERAN GURU DALAM MENINGKATKAN MOTIVASI BELAJAR SISWA PADA KELAS 3 (Studi pada Sekolah Dasar Negeri 106 Desa Pulung Rejo Kecamatan Rimbo Ilir Kabupaten Tebo) - Riski Dewi Utami; Nova Elsyra; Helva Rahmi; Mardansyah (Nusantara Hasana Journal, 2023)
In the implementation of the learning process a teacher has a very important role in encouraging students' interest in teaching and learning activities. One way that can increase students' interest in learning is to give praise to students who have a high interest in learning and provide reinforcement of motivation that is less enthusiastic in improving learning. The results of the study indicated that the State Elementary School 106 Pulung Rejo Village, Rimbo Ilir District, Tebo Regency has not been running well because teachers in grade 3 do not have the right learning model, the obstacles faced by teachers in increasing students learning motivation in grade 3 are low enthusiasm of students in participating in the process of learning activities. Efforts made by teachers in increasing students' learning motivation are to generate student motivation in participating in the process of learning activities.